Transformations in the landscape of primary health care during COVID-19: Themes from the European region. Issue 5 (May 2022) - Kumpunen, Stephanie; Webb, Erin; Permanand, Govin; ZHELEZNYAKOV, Evgeny; Edwards, Nigel; van Ginneken, Ewout; Jakab, Melitta
Highlights: Multidisciplinary collaborations managed the frontline emergency response. Vulnerable people's needs were prioritised for PHC medical and social outreach. Digital solutions for remote triage, consultations, prescriptions and monitoring enhanced PHC's response. Learning from the agility and innovation in PHC transformation should continue. Abstract: The COVID-19 pandemic has dramatically impacted primary health care (PHC) across Europe. Since March 2020, the COVID-19 Health System Response Monitor (HSRM) has documented country-level responses using a structured template distributed to country experts. We extracted all PHC-relevant data from the HSRM and iteratively developed an analysis framework examining the models of PHC delivery employed by PHC providers in response to the pandemic, as well as the government enablers supporting these models. Despite the heterogenous PHC structures and capacities across European countries, we identified three prevalent models of PHC delivery employed: (1) multi-disciplinary primary care teams coordinating with public health to deliver the emergency response and essential services; (2) PHC providers defining and identifying vulnerable populations for medical and social outreach; and (3) PHC providers employing digital solutions for remote triage, consultation, monitoring and prescriptions to avoid unnecessary contact. These were supported by government enablers such as increasing workforce numbers, managing demand through public-facing risk communications, and prioritising pandemic response efforts linked to vulnerable populations and digital solutions. We discuss the importance of PHC systems maintaining and building on these models of PHC delivery to strengthen preparedness for future outbreaks and better respond to the contemporary health challenges.